(3CUhd GdEjeGfs - (3eMeO Hf YHO GdhgGH Hf SdjeGf GdJejej GdfLOj,J (B1206 (3g` s
(3ChdgG (B:s
(3gPG cJGH CUhd GdEjeGf JCdja GdTjN YHO GdhgGH hbO RGO ajg HYV ChdGOg RjGOI MSfI bGd QMeg Gddg JYGdi (B: (3HGH eYQaI Gddg hGdEjeGf Hg s
(3BNQgG (B:s
(3aEf GdLhGR gh GdNjQ QhGgeG GHh OGhO hGddg CYde hGdMeO dgd QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B257s
(3eUOQ GbJfGA GdCUd (B:s
(3GdYGeI HGdQjGV(B(459 / 86) s
Keywords: (3GdJhMjO hGdedd hGdfMds